2020
DOI: 10.1016/j.nlm.2019.107128
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different protocols of physical exercise and rest on long-term memory

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 64 publications
(74 reference statements)
1
24
1
Order By: Relevance
“…An additional reason for our null findings may be that our chosen exercise intensity (high-intensity) was not optimal for enhancing memory. In conflicting past research, some studies suggested that high-intensity acute exercise may be more effective in enhancing memory while others found moderate-intensity acute exercise optimal (Pyke et al, 2020). Lastly, it remains possible that acute exercise has no causal effect on human memory beyond improved incidental encoding, as in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…An additional reason for our null findings may be that our chosen exercise intensity (high-intensity) was not optimal for enhancing memory. In conflicting past research, some studies suggested that high-intensity acute exercise may be more effective in enhancing memory while others found moderate-intensity acute exercise optimal (Pyke et al, 2020). Lastly, it remains possible that acute exercise has no causal effect on human memory beyond improved incidental encoding, as in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Another aspect that should be carefully considered in future work is the intensity of acute exercise. Based on meta-analytic findings [20], we intentionally chose a higher intensity bout of exercise, but recent work suggests that moderate-intensity exercise may optimally influence memory [26]. Given these conflicting findings, future work should consider evaluating intensity-specific effects of acute exercise on face-name memory.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors found opposite conclusions by showing higher benefits of an acute MICT session on memory performance than HIIT [117]. A meta-analysis by Chang et al (2012) showed that lower intensities would better improve cognitive performance immediately after an acute exercise completion (until 1 min) [118].…”
Section: In Humansmentioning
confidence: 98%